1985
DOI: 10.1099/00221287-131-3-651
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ethanol Degradation Pathways in Anoxic Freshwater Environments

Abstract: Pool sizes, turnover times and turnover rates of ethanol and acetate in anoxic sediments of Lake Mendota and Knaack Lake and in anoxic sewage digestor sludge were determined by gas chromatography-gas proportional counting techniques. Ethanol accounted for 6, 14 and 2.5 % of the total carbon flux to methane in these environments, respectively. The distribution of labelled carbon in the methane and carbon dioxide fractions obtained during incubation of the anoxic materials with C-1 and C-2 labelled acetate and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…Formation of acetate and propionate was also observed in another study using an ethanolfermenting bacterium (Samain et al 1982). Addition of hydrogen inhibited ethanol degradation and resulted in an accumulation of 14C-labeled butyrate (Schink et al 1985). Fermentation of ethanol to acetate and propionate by Desulfobulbus was strongly inhibited by high hydrogen concentrations (Schink, et al 1987).…”
Section: N-propanol Formation and Consumption During Ethanol Oxidatiomentioning
confidence: 78%
See 3 more Smart Citations
“…Formation of acetate and propionate was also observed in another study using an ethanolfermenting bacterium (Samain et al 1982). Addition of hydrogen inhibited ethanol degradation and resulted in an accumulation of 14C-labeled butyrate (Schink et al 1985). Fermentation of ethanol to acetate and propionate by Desulfobulbus was strongly inhibited by high hydrogen concentrations (Schink, et al 1987).…”
Section: N-propanol Formation and Consumption During Ethanol Oxidatiomentioning
confidence: 78%
“…Propionate consumption via reactions 3 and 4 was energetically favorable during this period. Propionate could have been formed from acetate (reaction 6), propanol (reaction 7), or ethanol (Schink et al 1985).…”
Section: -10mentioning
confidence: 99%
See 2 more Smart Citations
“…In the ethanol-fed columns, most likely only bacteria in the first column had ethanol to utilize as an energy source with the next two columns having to use acetate, which is a potential ethanol metabolite ) that was not monitored in our study, or have no energy source. Previous research indicated that the predominant ethanol degradation pathway is through the production of propionate through succinate using the hydrogen released from the oxidation of acetate, which has a no net-yield of reducing equivalents Schink et al, 1985).…”
Section: Pce Dechlorination In 1-d Columnsmentioning
confidence: 99%